@TedShifrin ... it is linear! For your sequence:
$$(x,x^4, x^2, x^2, x^3,\dots)$$
We write this as:
$$ K_0 =sx + s^2 x^4 + s^3 x^2 + s^4 x^3 + \dots \equiv A_0$$
Multiplying $s$
$$ s K_0 = 0+s^2 x + s^3 x^4 + s^4 x^2 \dots $$
Subtracting the equations:
$$ K_0(s-1) = -sx + s^2x(1-x^3) + s^3 x^2 (x^2 -1) + s^4 x^2(1-x)$$
Hence using $x^\lambda + y^\lambda = 2$
$$ K_0(s-1) = -sx + s^2x(y^3-1) + s^3 x^2 (1-y^2) + s^4 x^2(y-1)$$
Now using $xy=1$
$$ K_0(s-1) + sx + s^2x + s^3 +s^4 x^2 = s^2 x^{-2} + s^3 x^2 + s^4 x \equiv A_1$$